2020
DOI: 10.3389/fonc.2020.00291
|View full text |Cite|
|
Sign up to set email alerts
|

Long Non-coding RNA MIR570MG Causes Regorafenib Resistance in Colon Cancer by Repressing miR-145/SMAD3 Signaling

Abstract: An increasing number of studies have shown that long non-coding RNA (lncRNA) dysregulation plays a fundamental role in the development of various cancers, including colon cancer. Nonetheless, the mechanisms of lncRNA in regorafenib-resistance remain unclear. Our research revealed the lncRNA MIR570MG increased in regorafenib-resistant colon cancer cells compared to the regorafenib-sensitive cells. Furthermore, MIR570MG sponged miR-145, which declined in regorafenib-resistant colon cancer cell lines. More import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Additionally, some miRNAs are associated with resistance to regorafenib in experimental models. In fact, Wei et al showed that long non-coding RNA MIR570MG-sponged miR-145 causes resistance to regorafenib in mouse models of human CRC HCT116R [ 23 ]. The findings of Cai et al demonstrated in vitro that regorafenib treatment is associated with increased expression of miR-34a, highlighting this miRNA as a target for overcoming resistance to this specific treatment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some miRNAs are associated with resistance to regorafenib in experimental models. In fact, Wei et al showed that long non-coding RNA MIR570MG-sponged miR-145 causes resistance to regorafenib in mouse models of human CRC HCT116R [ 23 ]. The findings of Cai et al demonstrated in vitro that regorafenib treatment is associated with increased expression of miR-34a, highlighting this miRNA as a target for overcoming resistance to this specific treatment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some lncRNAs were reported to function as oncogenes or tumor suppressors in different types of cancers including CRC (Jin et al, 2020;Shang et al, 2020;Shen et al, 2020;Wang et al, 2020;Wei et al, 2020;Zheng et al, 2020). only few lncRNAs in CRC have been functionally characterized and the biological function of most of the lncRNAs remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This lncRNA acts as a sponge for miR-145 and inversely regulates the expression of miR-145. At this time, the expression of Smad3, a target of miR-145, increases, thereby promoting resistance to regorafenib [ 96 ]. The BRAF inhibitor vemurafenib is less effective in BRAF -mutated CRC.…”
Section: Molecular Targeted Therapeutic Drugs and Resistancementioning
confidence: 99%